The health perception of urban green spaces and its emotional impact on young adults: an empirical study from three cities in China - Wang, Jinsong; Liu, Nan; Zou, Jiaying; Guo, Yanlong; Chen, Hong (Frontiers in Public Health, 2023)
Exposure to green space can bring many benefits to physical and mental health, but in China, the attractiveness of green space to youth groups seems to be not significant. The question of how to encourage young people to go out of the house to better perceive green space, enjoy nature, and promote physical and mental health is on our minds. Therefore, this study combines young people's green space perception, green space use, and purpose of visit to explore its impact on the emotional health of youth groups, combined with the PANAS psychological data scale, an online questionnaire survey of 426 residents (18-35 years old) in three Chinese cities, and was used to construct a multiple regression model and AMOS structural equations.The results of the study showed that, firstly, environmental attractiveness, environmental odor, and number of facilities were the key factors influencing adolescents' landscape perception evaluation, while activity space, environmental odor, and environmental attractiveness had a greater impact on adolescents' emotional well-being. Second, among adolescents' visit purposes, socializing and fitness were more likely to help them generate positive emotions while resting and viewing activities were effective in helping them alleviate negative emotions. In addition, in terms of usage, residents who took public transportation as well as those who arrived on foot were the most emotionally healthy. The findings of this paper provide insights for public policymakers, urban planners, and landscape architects to better encourage youth participation in green spaces when they are installed.